Development of CT Metal Artifact Reduction Algorithm for use in Radiotherapy Treatment Planning System - Abdul Aziz, Mohd Zahri; Osman, Noor Diyana; Salikin, Md Saion; Yusoff, A.L. (2011)
Computed Tomography (CT) images serve many benefit in radiology as well as radiotherapy treatment. Unfortunately the metal type inhomogeneities such as metal amalgam results a metal streak artifact in the images and thus raise errors in treatment planning system (TPS) [1,2]. In radiotherapy errors of radiation delivery can cause various side effects to patient. For this reason a metal artifact reduction (MAR) algorithm was developed in MATLAB platform to give a satisfaction in image quality and thus to TPS.